Raindance producers' lab : lo-to-no budget filmmaking - Grove, Elliot (Focal Press, 2014)
"Discover vital insider tips on producing movies with a micro budget! Covering both tried and true filmmaking techniques as well as insight on marketing, selling, and distributing your film, Raindance Producers' Lab, Second Edition is the ultimate independent filmmaker's guide to producing movies. This edition has been updated to include: fresh features on low-budget, high quality video cameras, including new digital camera options such as DSLRAn extensive selection of new case studies and interviews with industry talents such as Ewan McGregor, Ate de Jong, James Youngs, Joe Pavlo, Martin Myers, Rolin Heap, and more; essential advice on how to make the web work for you and promote your films through Twitter, Facebook and other social media platformsAll new postproduction workflows. A companion website (www.lotonobudgetfilmmaking.com) providing all the contracts and material you need to run a production company and make successful low budget movies. The verdict is in: if you're looking for a clear-cut, no-nonsense approach to micro-budget filmmaking and producing, Elliot Grove's wealth of teaching and filmmaking experience combined with winning formulas for marketing and promotion make this book a must-have one-stop shop for filmmakers! "--